Underwriting bank bonds: Information sharing, certification and distribution networks - Carbo-Valverde, Santiago; Rodriguez-Fernandez, Francisco; Saunders, Anthony (Journal of Corporate Finance, 2021)
A unique but mostly unexplored feature of banks in debt markets is that they can either self-issue or use third-party underwriters. We analyze the importance of information sharing concerns, the need for certification and the value of underwriter distribution networks in two debt underwriting frameworks: the bank choice of self-underwriting versus third-party underwriting, and whether the bond is underwritten by a reputable bank. Exploring some specific structural features of European bank bond deals, we find that information sharing concerns are significantly related to the probability of self-issuance. The results also show that the need for certification, previous underwriting experience, issuer relationships with reputable underwriters and underwriter distribution capacity are particularly relevant for bank bonds underwritten by reputable banks.